Blood Pressure Measurement in SPRINT (Systolic Blood Pressure Intervention Trial). Issue 5 (May 2018) - Johnson, Karen C.; Whelton, Paul K.; Cushman, William C.; Cutler, Jeffrey A.; Evans, Gregory W.; Snyder, Joni K.; Ambrosius, Walter T.; Beddhu, Srinivasan; Cheung, Alfred K.; Fine, Lawrence J.; Lewis, Cora E.; Rahman, Mahboob; et al.
Abstract : Recent publications have stated that the blood pressure (BP) measurement technique used in SPRINT (Systolic Blood Pressure Intervention Trial) was unattended. However, the SPRINT protocol does not address the issue of attendance. A survey was conducted immediately after SPRINT closeout visits were completed to inquire whether BP measurements were usually attended or unattended by staff. There were 4082 participants at 38 sites that measured BP after leaving the participant alone the entire time (always alone), 2247 at 25 sites that had personnel in the room the entire time (never alone), 1746 at 19 sites that left the participant alone only during the rest period (alone for rest), and 570 at 6 sites that left the participant alone only during the BP readings (alone for BP measurement). Similar systolic and diastolic BPs within randomized groups were noted during follow-up at the majority of visits in all 4 measurement categories. In the always alone and never alone categories, the intensive group had a similarly reduced risk for the primary outcome compared with the standard group (hazard ratio, 0.62; 95% confidence interval, 0.51–0.76 and hazard ratio, 0.64; 95% confidence interval, 0.46–0.91, respectively; pairwise interaction P value, 0.88); risk was not significantly reduced for the intensive group in the smaller alone-for-rest and the alone-for-BP-measurement categories. Similar BP levels and cardiovascular disease risk reduction were observed in the intensive group in SPRINT participants whether the measurement technique used was primarily attended or unattended. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01206062. Abstract : Supplemental Digital Content is available in the text.